Age- and sex-specific first health care use for migraine in 2016 in children and adolescents from prospectively collected health insurance data in Germany. (August 2019) - Albers, Lucia; Kries, Rüdiger von; Straube, Andreas; Heinen, Florian; Landgraf, Mirjam N; Obermeier, Viola; Ruscheweyh, Ruth
Background: Migraine in children and adolescents is associated with significant disability and a high risk of persistence into adulthood. Objective: Data on migraine incidence in children and adolescents are few and relatively coarse. To tailor interventions starting shortly after disease onset, detailed information on age- and sex-specific incidence of migraine in children and adolescents is needed. Methods: We used health care data prospectively collected by the BARMER statutory health insurance, representing ∼11% of the German population. The incidence of migraine diagnoses (International Classification of Diseases (ICD)-10 code G43) in the year 2016 was assessed in subjects aged 0–19 years, who had been continuously insured with the BARMER between 2005 and 2016 or during their entire lifespan. Results: Data from ∼1.2 million children and adolescents were available. The incidence of migraine diagnoses steadily increased with age, reaching ∼1% per year around the age of 10 for both sexes, and 3.49% per year in females and 1.72% per year in males at the age of 19. Incidences in males and females were similar up to the age of 13 and higher in females from there on. The proportion of incident migraine diagnoses specified as "definite" versus "probable" migraine increased with age. Conclusion: The present study provides a representative estimation of the first documented health care use for migraine in children and adolescents in Germany within 1-year age bins, separately for boys and girls. These data will be helpful for tailoring early healthcare interventions to reduce disability and prevent migraine chronification.